EFFECT OF HUMANISTIC EXISTENTIAL THERAPY TOWARD INCREASING SELF CONCEPT AND SOCIAL INTERACTION ALSO DECREASED ANXIETY ON PEOPLE WHO HAVE HAD LEPROSY (OYPMK) AT PERMATA VILLAGE,BONE BOLANGO REGENCY - Dewi Modjo (-, 2021)
The purpose of this study was to determine the effect of humanistic existential therapy to increase self-concept and social interaction and also decreased anxiety on people who have had leprosy (OYPMK) at Permata Village, Bone Bolango Regency. The method of  this  research  is  pre-Experimental  with  one  group  pretest-posttestdesign.  the population is 26 peoples who have had leprosy (OYPMK) at Permata Village, Bone Bolango Regency. The sample in this research is total sampling. Statistical test of P- value 0.000 of the self-concept variable,social interaction variable andanxiety variable so it can be concluded there is an effect of humanistic existential therapy to increase self-concept and social interaction and also decreased anxiety on people who have had leprosy (OYPMK) at Permata Village, Bone Bolango Regency.